Dumbing Down The Crisis of Quality and Equity in a Once-Great School System-and How to Reverse the Trend - Henrekson, Magnus; Wennström, Johan (Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This open access book examines the challenges and issues caused by a move to a marketized education system in Sweden. Observing the introduction of the school voucher system and a postmodern social constructivist view of knowledge, the move away from objective knowledge is identified as the core reason for Sweden's current education crisis. The impact of declining education standards on the labor market is also discussed. This book highlights the issues seen in Sweden and suggests policies that can improve education in the rest of the Western world as well. It will be relevant to students and researchers interested in education and labor economics. .